Evaluating the Impact of Professional Development on STEAM Education Competency in the Industrial Revolution 5.0 Era - Suhendro, Eko; Mubin, Muhammad Nurul; Saharani, Anita (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This research evaluates the impact of the Teacher Professional Education (PPG) program for Kindergarten educators on their understanding of Science, Technology, Engineering, Arts, and Mathematics (STEAM) education in the context of the Industrial Revolution 5.0 and Society 5.0. Utilizing a quantitative approach with a pretest-posttest design, the study involved fifty kindergarten teachers from the PPG Daljab (In-Service Teacher Professional Education) at FITK, UIN Sunan Kalijaga. The assessment of participants, conducted through validated instruments, focused on measuring the enhancement of pedagogical competencies in STEAM before and after the program. Results indicated a notable improvement in the teachers' competencies post-intervention. The statistical analysis, including a paired t-test, showed a significant increase in test scores from the pretest to the post-test with a t-statistic of -53.58 and a p-value of 8.54 x 10^-44, highlighting a highly significant difference and validating the effectiveness of the PPG program in bolstering STEAM educational skills. Further tests for normality and homoscedasticity confirmed the reliability and validity of the data. Despite these positive outcomes, variations in test item reliability suggest the need for ongoing evaluation and refinement of assessment tools. The study underscores the potential of structured professional development programs in enhancing teacher capabilities, particularly in adapting to the demands of modern technological and interdisciplinary educational environments. It recommends further research to explore the long-term effects of such interventions on teacher competencies and to fine-tune the assessment methodologies used. This study contributes to the understanding of effective professional development in preparing educators to integrate and excel in STEAM disciplines, aligning with the educational imperatives of contemporary technological revolutions.